Topical steroids more abused than used! A cross-sectional study in the outpatient department of dermatology in a tertiary care centre in coastal Karnataka - Nagaraj, Rashmitha; Nagaraj, Shruthi Hassan (International Journal of Research in Dermatology, 2019)
Background: Topical corticosteroids (TCS) are one among the most commonly prescribed medications in the ambulatory setting. They exhibit anti-inflammatory effects, immunosuppressive effect, antiproliferative effects and vasoconstriction. Methods: A total of 400 patients who had visited the outpatient department or was admitted in the department of dermatology and had applied topical corticosteroids for a duration of 2 or more weeks were included for the study over a period of 2 months in June and July 2018. This study is clinical and observational, to evaluate the topical corticosteroids abuse cases. Results: Out of 400 people 304 [76%] patients were either recommended or prescribed TCS by a non-physician source. And the rest 96 [24%] patients were been prescribed by the medical fraternity. Majority of patients have applied TCS belonging to super potent class [294/400] duration of usage varied from 2 weeks to 2 years and amount from 10 to 240 g. The most common consequences of TCS abuse was rebound phenomenon followed by hypopigmentation, striae. Conclusions: Prolonged and continuous use of TCS can cause many adverse effects with varying clinical presentation. Treatment is difficult as there is rebound phenomenon with discontinuation of TCS. Gradual withdrawals of TCS with supplementation of adequate treatment to the present clinical issue are usually recommended to get good clinical results.